Correlation of Fine Needle Aspiration Cytology With Thyroid Function Test in Tertiary Care Hospital, Kathmandu - Paudel, Deliya; Pokhrel, Sushant; Adhikari, Dibit; Regmi, Himanshu (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: FNAC is the gold standard method in the management of thyroid lesions and helps to rule out the surgical cases. Thyroid disorders show different abnormal thyroid function test. This study aims to find the association between thyroid function test and FNAC. Methods: This cross-sectional study was conducted in 137 patients with thyroid swelling that attended in Manmohan Memorial Medical College and Teaching Hospital (MMTH). Thyroid lesion were evaluated by cytologically and compared with thyroid function test. Result: Among the study population, 44.4% of patients presented with colloid goitre while 38.3% with lymphocytic thyroiditis. Age group of 30-40 years showed higher prevalence of thyroid lesion. 40.6% of the study population were had thyroid function test. About half of the lymphocytic thyroiditis had hypothyroidism with positive anti-thyroid peroxidase. Conclusion: This study showed that having normal thyroid function test also presented with different types of thyroid lesion. Hence, we conclude that FNAC and TFT should be performed for the proper management of thyroid lesion.